A dual-adjuvanting strategy for peptide-based subunit vaccines against group A Streptococcus: Lipidation and polyelectrolyte complexes. Issue 24 (15th December 2020) - Zhao, Lili; Yang, Jieru; Nahar, Ummey Jannatun; Khalil, Zeinab G.; Capon, Robert J.; Hussein, Waleed M.; Skwarczynski, Mariusz; Toth, Istvan
Graphical abstract: Abstract: In order to improve the immunogenicity of peptide-based vaccines against group A Streptococcus (GAS), lipid moieties (C16 lipoamino acid and cholic acid) were conjugated with peptide antigen (P25-J8) and further modified with α-poly(glutamic acid) (α-PGA). Thus, positively charged lipopeptide vaccine candidates LCP-1 (P25-K(J8)-SS-C16-C16) and LCP-2 (P25-K(J8)-SS-K(cholic acid)) were synthesized. Negatively charged LCP-3 (P25-K(PGA-J8)-SS-K(cholic acid)) was also produced by attaching α-PGA to the J8 N -terminus of LCP-2. Polyelectrolyte complex (PEC) nanoparticles were formulated with heparin and/or trimethyl chitosan (TMC) for delivery of the lipopeptide vaccine candidates. The ability of the antigen-loaded nanoparticles to induce humoral immune responses was examined in outbred female Swiss mice following intranasal immunization. The antibodies produced were opsonic against all clinical GAS isolates tested.